PREFERENSI KONSUMEN TERHADAP PANCAKE DARI TEPUNG SUKUN - Sitti Rosipah; Burhan Burhan; Umi Purwandari (AGROINTEK, 2013)
Preference of food product is influenced by personal characteristics (age, sex,education, income, and nutrient knowledge), food characteristics (taste, shape, and texture) andalso surroundings characteristics (job, number of family, mobility, and season). Pancake hassome attributes such as texture, colour, taste, and aroma. These attributes will influenceconsumer likes. The aims of this research are to determine the attributes of consumerpreference appraisal and to know the order of consumer preference toward pancake made ofbreadfruit flour. The method used in this research is conjoint analysis. Attributes and theirlevel is determined by asking for some respondents (questionaire) to collect data of consumerpreference of this product. The results (measured by utility value) of this research are: texture(rather soft) 0,029; colour (golden yellow) 0,112; taste (sweet) 0,021; and aroma (usual) 0,566.The priority of consumer’s decision making toward pancake made of breadfruit are: aroma(49,745%), texture (19,925%), colour (19,628%), and taste (10,702%).